Hydroxyvitamin D assays: An historical perspective from DEQAS. Issue 177 (March 2018) - Carter, G.D.; Berry, J.; Durazo-Arvizu, R.; Gunter, E.; Jones, G.; Jones, J.; Makin, H.L.J.; Pattni, P.; Sempos, C.T.; Twomey, P.; Williams, E.L.; Wise, S.A.
Highlights: DEQAS is an international Quality Assessment Scheme for vitamin D metabolites which works closely with the Vitamin D Standardization Program (VDSP). The scheme was launched in 1989 and the results can be used to monitor the changes in methods used and their performance. The most significant development in the measurement of 25- hydroxyvitamin D was the introduction of fully automated assays run on existing clinical chemistry analyzers. DEQAS became an accuracy-based scheme in 2013 and the accuracy of methods and participants' results are assessed against the 'true' value assigned by the National Institute of Standards and Technology (NIST) using their reference measurement procedure. Overall accuracy has shown an improvement but the fully automated immunoassays show a sample to sample variation in bias which is greater than that given by HPLC/UV and LC–MS/MS methods. Abstract: Recent years have seen a substantial increase in demand for 25-hydroxyvitamin D (25-OHD) assays. DEQAS (the Vitamin D External Quality Assessment Scheme) has been monitoring the performance of these assays since 1989. The first DEQAS distribution was in June 1989 and results were submitted by 13 laboratories in the UK, two of which used HPLC/UV; the rest used ligand binding assays with a tritium tracer. Inter-laboratory CVs (ALTM) ranged from 29.3% (42.7 nmol/L) to 53.7% (20.0 nmol/L). Currently the scheme has participants in 56 countries using 30 methods or variants of methods. In January 2017, 918 participants returned results and inter-laboratory CVs (ALTM) ranged from 10.3% (73.1 nmol/L) to 15.3% (29.4 nmol/L). Over the last 27 years, there have been a number of significant milestones in assay development. The first major advance was the development of an iodinated 25-OHD tracer by Hollis and Napoli in 1992, subsequently used in an RIA kit marketed by DiaSorin. This and other commercial radioimmunoassays that followed brought 25-OHD assays within reach of many more non-specialist routine laboratories. With the introduction of fully automated non-isotopic assays without solvent extraction, measurement of 25-OHD became available to any clinical chemistry laboratory with an appropriate analytical platform. However, as the limitations of these non-extraction assays became apparent more laboratories started using LC–MS/MS methodology. Meanwhile the variable accuracy of 25-OHD methods has been addressed by the Vitamin D Standardization Program (VDSP) which encourages manufacturers to produce methods traceable to the reference measurement procedures (RMPs) of NIST, University of Ghent and the Centers for Disease Control and Prevention (CDC). DEQAS changed to an accuracy-based scheme in 2013 and now assesses assay accuracy against the NIST RMP. This review will use DEQAS results and statistics to chart the historical development in 25-OHD assay technology and highlight some of the problems encountered in obtaining reliable results for this most challenging of analytes.